The New Conflict of the Faculties: Kant, Radical Enlightenment, The Hyper-State, and How to Philosophize During a Pandemic - Hanna, Robert (Con-Textos Kantianos. International Journal of Philosophy, 2021)
In this essay, I apply the Kantian (or at the very least, Kant-inspired) interpretation of enlightenment as radical enlightenment to the enterprise of philosophy within the context of our contemporary world-situation, and try to answer this very hard question: “As radically enlightened Kantian philosophers confronted by the double-whammy consisting of what I call The Hyper-State, together with the 2020-2021 COVID-19 pandemic, what should we dare to think and do?” The very hard problem posed by this very hard question is what I’ll call The New Conflict of the Faculties. By way of a direct answer to this very hard question and by way of an effective solution to this very hard problem, I provide seven recommendations.